Chrysoeriol derivatives and other constituents from Glandularia selloi - Vestena, Angelica; Comerlato, Luana; Bridi, Henrique; Guerini, Leticia; Ccana-Ccapatinta, Gari Vidal; Vignoli-Silva, Marcia; Apel, Miriam Anders; Fernandes, Saulo; Castro-Gamboa, Ian [UNESP]; Silveira Zuanazzi, Jose Angelo; von Poser, Gilsane Lino (Elsevier B.V., 2019)
Glandularia selloi (Verbenaceae) presents phenylethanoids, iridoids and flavone glycosides as the main constituents. Two novel chrysoeriol derivatives, selloiside A (1) and selloiside B (2) were isolated from the methanolic extract of the aerial parts. Both flavones are acylated disaccharides. Two known compounds, verbascoside (3) and 6 beta-hydroxy-ipolamiide (4), were isolated from the methanolic extract of the roots. The structures were elucidated using 1D, 2D NMR and MS. Acylflavones have taxonomic significance since they occur mainly is species from the order Lamiales, specifically from the family Lamiaceae, closely related to Verbenaceae. The compounds 1 - 4 and the methanolic extract were investigated for antichemotactic activity.
Keywords: Glandularia selloi; acylated flavones; phenylethanoid glycosides; iridoids